2022
DOI: 10.1111/are.15864
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cumin ( Cuminum cyminum ) and lavender ( Lavandula angustifolia ) essential oils as anaesthesics in common carp ( Cyprinus carpio L.1758)

Abstract: In this study, anaesthetic effects of cumin and lavender essential oils by comparing with clove oil were determined on common carp. Fish (mean weight of 10 g) were exposed to nine concentrations of essential oils (5–500 mg L−1). Anaesthesia induction, recovery times and mean lethal dose of essential oils (10 min LC50 concentration) were evaluated separately for each fish. In addition, histopathological effects of essential oils on the fish tissues including hepatopancreas, gill and skin were investigated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…The anesthetic efficacy of lavender essential oil has been extensively investigated across various fish species (Can and Sümer, 2019;Raisi et al, 2020;Metin et al, 2022;Yigit et al, 2022;Thabet et al, 2023). Can and Sümer (2019) Conversely, Raisi et al (2020) reported the inefficacy of high concentrations (600 and 1200 mg L -1 ) of L. officinalis oil in inducing anesthesia in Cichlasoma nigrofasciata.…”
Section: Resultsmentioning
confidence: 99%
“…The anesthetic efficacy of lavender essential oil has been extensively investigated across various fish species (Can and Sümer, 2019;Raisi et al, 2020;Metin et al, 2022;Yigit et al, 2022;Thabet et al, 2023). Can and Sümer (2019) Conversely, Raisi et al (2020) reported the inefficacy of high concentrations (600 and 1200 mg L -1 ) of L. officinalis oil in inducing anesthesia in Cichlasoma nigrofasciata.…”
Section: Resultsmentioning
confidence: 99%
“…Anise essential oil has been demonstrated anaesthetic effect on zebrafish (Seyidoglu and Yagcılar 2020 ). In previous studies, different plant essential oils and active components have been studied as anaesthetic in common carp (Roohi and Imanpoor 2015 ; Mirghaed et al 2016 ; Mazandarani and Hoseini 2017 ; Mazandarani et al 2017 ; Rakhshani et al 2018 ; Khumpirapang et al 2018 ; Yousefi et al 2018a , 2018b ; Al-Niaem et al 2019 ; Krasteva et al 2021 ; Metin et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%